2003
DOI: 10.3109/10606820308263
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Signaling Mechanisms for Muscarinic Acetylcholine Receptors

Abstract: Signaling pathways for muscarinic acetylcholine receptors (mAChRs) include several enzymes and ion channels. Recent studies have revealed the importance of various isoforms of both alpha and betagamma subunits of G proteins in initiation of signaling as well as the role of the small monomeric G protein, Rho, in the activation of phospholipase D. Modulation of adenylyl cyclase activity by mAChRs appears more diverse as the interaction of various receptor subtypes with the many isoforms of the enzyme are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 271 publications
0
46
0
3
Order By: Relevance
“…Among the mAChRs, M 1 is most abundantly expressed in the hippocampus, cortex, and striatum, and localizes to postsynaptic membranes (3), where it signals via G q /G 11 G-proteins to phospholipase C and through other G-proteins to additional signaling systems (4,5). M 1 regulates several ion channels including KCNQ inwardly rectifying K ϩ currents, voltage-gated calcium channels, and NMDA receptors (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Among the mAChRs, M 1 is most abundantly expressed in the hippocampus, cortex, and striatum, and localizes to postsynaptic membranes (3), where it signals via G q /G 11 G-proteins to phospholipase C and through other G-proteins to additional signaling systems (4,5). M 1 regulates several ion channels including KCNQ inwardly rectifying K ϩ currents, voltage-gated calcium channels, and NMDA receptors (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Recombinant HCN channel function can be modulated by activation of mAChRs (Pian et al, 2007). Thus, PIP 2 -gated HCN3 channels in the IGL may represent an important target for drugs acting at the mAChR signaling pathway (Lanzafame et al, 2003).…”
Section: Functional Expression Of Hcn3 Channels Contributes To Rhythmmentioning
confidence: 99%
“…[12] Myometrium is innervated by cholinergic parasympathetic fibers and acetylcholine activates the M 2 receptors to bring about the contractions. [13] It has been shown that uterotonic activity of Ficus asperifolia extracts increased uterine contractility involving cholinergic (muscarinic) mechanism. [14] Our observations indicate that BPA exposure decreased.…”
Section: Discussionmentioning
confidence: 99%